Pengaruh Kualitas Pelayanan dan Citra Merek Terhadap Kepuasan Pelanggan dan Dampaknya Kepada Loyalitas Pelanggan Pupuk Kujang - Wahyu Murti; Gideon Patra Dikto (Jurnal Manajemen FE-UB, 2020)
This study aims to determine the effect of service quality and brand image on customersatisfaction and its impact on customer loyalty of Pupuk Kujang. The data used in this study areprimary data obtained from the distribution of questionnaires to official distributors of PupukKujang in DKI Jakarta, Banten, West Java and Central Java. The data processing method usesthe path analysis method with the help of the SPSS 24 program. The results of this study show thatthe quality of service directly has a positive and significant effect on customer satisfaction, brandimage directly has a positive and significant effect on customer satisfaction. The results of substructure II research concluded that service quality directly has a positive and significant effecton customer loyalty, brand image directly has a positive and significant effect on customerloyalty, and customer satisfaction directly has a positive and significant effect on customerloyalty. The results of the mediation test concluded that service quality indirectly has a positiveand significant effect on customer loyalty through job satisfaction and brand image indirectly hasa positive and significant effect on customer loyalty through job satisfaction.Keywords: Service quality, Brand Image, Customer Satisfaction, Customer Loyalty